Experimental quantification of the operative time of a passive HVAC system using porous covering materials - José A. Orosa (2010)
Permeable coverings are porous materials that improve partial vapor pressure and thereby the agreeable nature of the indoor environment and local thermal comfort, while also saving energy. This is a consequence of the damping effect of materials on air humidity and is determined by the rate at which real buildings absorb moisture. This rate cannot be predicted using sorption isotherm data and has to be obtained experimentally. A new experimental method to obtain the real storage capacity and rate of sorption of covering materials is presented. A significance analysis showed that permeable coverings have an effect in indoor air conditions, not only during the first hours of occupation but also throughout the day. The maximum effect occurs during the early period (between 0900 LT and 1400 LT) and includes the 4-hour period after the office is closed. The results show that the sorption of water vapor in the porous envelope has a greater effect on indoor humidity than ventilating the room with 0.5 ach.